Clinical profile and outcome of organ dysfunction in sepsis - Dash, Laxmikanta; Singh, Lagendra Kumar; Murmu, Malati; P., Susruth Krishnadas; Kerketta, Amita; Hiregoudar, Mrutyunjay B. (International Journal of Research in Medical Sciences, 2018)
Background: Sepsis is defined as life threatening organ dysfunction due to a dysregulated host response to infection. It is the tenth leading cause of death among older adults in United States. Mortality rate of the sepsis ranges from 30-40%. In severe cases sepsis can drastically reduce blood flow to the major organs, leading eventually to septic shock, widespread organ failure and death. So, the present study was done to evaluate the clinical profile, symptoms, source of infection, co-morbid conditions and outcome with respect to the organ dysfunction in sepsis cases. Methods: This prospective observational study was undertaken among 100 cases of sepsis diagnosed by the “International Sepsis Definitions Conference” criteria admitted during October 2015 to September 2017. All patients were evaluated clinically and subjected for laboratory investigations. Results: In present study, a total of 100 cases were enrolled. Mean age of cases were 38.15 years. Male and female ratio was 1.63:1. Most common symptom was fever (100%). Pneumonia was the most common (36%) source of infection. Mortality was highest in pneumonia (55.55%). 77 % of cases had organ dysfunction. Cardiovascular system was the most common system involved. Maximum mortality was within the age group of 56-65 years. Diabetes was the most common co-morbid condition. Mean APACHE II score was high among the death cases. Conclusions: Sepsis was more common in younger group of patients but mortality was more in elderly age group. Overall mortality was 38%.